2014
DOI: 10.1016/b978-0-12-800255-1.00005-3
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Role of Plg-RKT in Macrophage Recruitment

Abstract: Plasminogen is the zymogen of plasmin, the major enzyme that degrades fibrin clots. In addition to its binding and activation on fibrin clots, plasminogen also specifically interacts with cell surfaces where it is more efficiently activated by plasminogen activators, compared with the reaction in solution. This results in association of the broad spectrum proteolytic activity of plasmin with cell surfaces that functions to promote cell migration. Here we review emerging data establishing a role for plasminogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 197 publications
(292 reference statements)
1
37
0
Order By: Relevance
“…The activation of pro-uPA and plas-minogen are greatly enhanced when both are bound to the cell surface (15,48). On monocytes-macrophages, the plasminogen receptors Plg-R KT (45,49) and annexin A2 (50) are co-localized with uPAR (and presumably uPA), with this proximity being central to the reciprocal cell surface activation of uPA and plasmin (45). For the RgpA-Kgp complex to activate pro-uPA to uPA and/or plasminogen to plasmin, it would presumably have to be in very close proximity to the cell-surface uPAR-uPA and plasminogen "complex."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of pro-uPA and plas-minogen are greatly enhanced when both are bound to the cell surface (15,48). On monocytes-macrophages, the plasminogen receptors Plg-R KT (45,49) and annexin A2 (50) are co-localized with uPAR (and presumably uPA), with this proximity being central to the reciprocal cell surface activation of uPA and plasmin (45). For the RgpA-Kgp complex to activate pro-uPA to uPA and/or plasminogen to plasmin, it would presumably have to be in very close proximity to the cell-surface uPAR-uPA and plasminogen "complex."…”
Section: Discussionmentioning
confidence: 99%
“…Because macrophages express high levels of uPAR and various receptors for plasminogen (e.g. annexin A2 and Plg-R KT ) (44,45), thereby localizing the activation of pro-uPA and plasminogen to the cell surface (4), it is likely that the gingipain complex is acting in close proximity to the cell surface uPAR-uPA complex. Indeed, it is known that Kgp binds vitronectin, a component of the extracellular matrix and a ligand for uPAR (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…1 F ortunately, most patients with advancedstage Hodgkin lymphoma are cured with front-line standard chemotherapy. 2,3 In the United States, the combination of doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) is generally considered the preferred regimen to treat these patients secondary to multiple large phase 3 studies that have demonstrated significant efficacy of the regimen combined with fewer toxicities when compared with more aggressive regimens.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Up to 30% of patients are not cured with initial ABVD therapy, as evidenced by a reported 10-year progression-free survival (PFS) rate of 69%. 2 These patients with relapsed/ refractory disease require treatment with aggressive therapy, often including salvage chemotherapy and stem-cell rescue. Even with these therapies, only ;50% of these patients are alive and disease free 10 years after treatment.…”
Section: 3mentioning
confidence: 99%
“…1998; Cesarman‐Maus & Hajjar 2005; Miles et al . 2014). Ligneous membranitis (LM) is a rare chronic inflammatory disease associated with congenital plasminogen deficiency.…”
mentioning
confidence: 99%